From neurological soft signs to functional outcome in young individuals in treatment with secondary services for non-psychotic disorders: a path analysis. Issue 7 (5th January 2017) - Minichino, A.; Francesconi, M.; Carrión, R. E.; Delle Chiaie, R.; Bevilacqua, A.; Parisi, M.; Rullo, S.; Bersani, F. S.; Biondi, M.; Cadenhead, K.
Abstract : Background: Functional decline among patients with mental illness is not unique to individuals with psychotic disorders. Despite this, research on early predictors of functional outcome mainly focused on individuals thought to have an 'at risk mental state' (ARMS) for psychosis. There is evidence suggesting that certain early vulnerability markers, such as neurological soft signs (NSS), may explain variability in functional outcomes independent of the level of psychosis risk and the traditional diagnostic classification. Method: Structural equation modeling was applied to baseline data from a prospective longitudinal study of 138 young individuals in treatment with secondary services for non-psychotic disorders. We evaluated theoretically based models of pathways to functional outcome starting from NSS. The intervening variables were established according to previous evidence and drawn from two general categories: cognition (neuro- and social-) and negative symptoms (expressive and experiential). Results: A final trimmed model was a single path running from NSS to neurocognition to experiential negative symptoms to outcome. It could not be improved by adding or dropping connections that would change the single path to multiple paths. The indirect effect from NSS to outcome was significant. The validity of the model was independent of the ARMS status and the psychiatric diagnosis. Conclusions: Our results provide evidence for a single pathway model in which the starting and intervening variables represent modifiable trans-diagnostic therapeutic targets to improve functional trajectories in young individuals with a recent-onset psychiatric diagnosis and different levels of psychosis risk.